A New Paradigm for Budgetary Financing of Patronized Goods in the Humanities and Social Sector: Evidence from Russian Regions - Rubinstein , Alexander Ya.; Славинская, Ольга; Burakov, Nikita (Economy of Regions, 2026)
This article examines the production and consumption of patronized goods in the humanities and social sector, including science, education, healthcare, and culture, as critical domains for social investment in human capital. These goods often do not align with standard market mechanisms, and existing theoretical approaches offer limited guidance on the nature and economic mechanisms of government support. We propose a new theoretical and methodological approach to financing the humanities and social sector, grounded in the characteristics of creative labour and the principles of W. Baumol’s “cost disease” theory. A parametric model of budget subsidies is proposed, grounded in the concept of “consolidated income” and incorporating a novel composite price index. In this model, state subsidies are treated as social investments designed to offset income losses of organizations due to their societal significance. The model incorporates two key normative conditions: N₁, reflecting the alignment of total labour productivity with macroeconomic indicators of a Russian region, and N₂, regulating the average monthly wages of employees. Testing the model on statistical data from 80 regions of the Russian Federation for 2015–2019 confirmed a persistent lag in total labour productivity in most theatrical organizations. Only 20 of the 80 regions saw productivity in the theatre sector exceed the regional average, while the average underfunding of the sector exceeded 50 % over the given period. These results underscore the need to increase the share of budget funds in the normative consolidated income to satisfy conditions N₁ and N₂, ensuring the effective operation of organizations. Growth in budget subsidies is shown to be crucial for preventing hyperinflationary ticket price increases and maintaining the affordability of publicly supported goods. The study concludes that normative subsidies aimed at supporting labour productivity growth effectively standardize wages and cover essential non-wage expenses in the humanities and social sector.